Comparison of breastfeeding, music therapy, and oral sucrose's impact on pain relief among infants during pentavalent vaccination - Harwinder Kaur; Gopal Singh Charan; Ravneet Kaur; Gursharn Singh Narang; Mandeep Singh Khurana (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Vaccination is a quick, safe, and effective way to avoid contracting hazardous diseases, but it often causes pain and discomfort. Various pharmacological and non-pharmacological pain management techniques are used to treat pain. This study aimed to compare the effectiveness of breastfeeding, musical therapy, and oral sucrose in infant's pain relief during pentavalent vaccination. MATERIALS AND METHODS: A quasi-experimental posttest-only research design was used. A total of 150 infants were enrolled using the purposive sampling technique (50 in the breastfeeding, 50 in the musical therapy, and 50 in the oral sucrose groups) coming for the first, second, and third doses of pentavalent vaccination. The data were collected using observation and the Neonatal Infant Pain Scale (NIPS). The results were calculated by descriptive and inferential statistics. RESULTS: The study revealed that half of the infants in the breastfeeding group felt severe pain, whereas the majority of infants in the musical therapy and oral sucrose groups felt severe pain during pentavalent vaccination. The median pain score in breastfeeding, musical therapy, and oral sucrose was 4.50, 6, and 7, respectively. Breastfeeding was significantly different from both musical therapy and oral sucrose in terms of pain scores. However, no significant difference was observed between musical therapy and oral sucrose. Overall, the results indicate that breastfeeding had a distinct impact on pain relief during pentavalent vaccination compared with the other interventions, while musical therapy and oral sucrose did not differ significantly in their effectiveness. CONCLUSION: The study concluded that breastfeeding is a safe, reliable, cost-effective, and easily accessible method to relieve an infant's pain during pentavalent vaccination. It is a simple method to alleviate pain among infants during vaccination.